Prefrontal Inositol Triphosphate Is Molecular Correlate of Working Memory in Nonhuman Primates. - López-Téllez, Juan Félix; López-Aranda, Manuel Francisco; Navarro-Lobato, Irene; Masmudi-Martín, Mariam; Martín-Montañez, Elisa; Blanco-Calvo, Eduardo; Khan, Zafar U. (Society for Neuroscience, 2010)
Working memory (WM) is a process of actively maintaining information in the mind for a relatively short period of time, and prefrontal cortex (PFC) has been thought to play a central role in its function. However, our understanding of underlying molecular events that translate intoWMbehavior remains elusive. To shed light on this issue, we have used three distinct nonhuman primate models of WM where each model represents three WM conditions: normal control, WM-deficient, and recuperated to normal from WM deficiency. Based on the hypothesis that there is a common molecular substrate for the coding ofWMbehavior, we have studied the relationship of these animals’ performance on aWMtask with their PFC levels of molecular components associated with Gq-phospholipase C and cAMP pathways, with the idea of identifying the footprints of such biomolecules. We observed that in all of the primate modelsWMdeficiency was strongly related to the reduced concentration of IP3 in PFC, whereas recuperation of WM-deficient animals to normal condition was associated with the normalization in IP3 level. However, this correlation was absent or weak for cAMP, active protein kinase A, dopamine D1 receptor, and Gq protein. In addition, WM deficiency related not only to pharmacological conditions but also to aging. Thus, it is suggested that optimal IP3 activity is essential for normalWMfunction and the maintenance of intracellular IP3-mediated Ca2 level in PFC may serve as biochemical substrate for the expression ofWMbehavior.
Keywords: Memoria - Aspectos fisiológicos; Corteza cerebral; Fosfolípidos; Primates; Working memory; Prefrontal cortex; Inositol triphosphate (IP3); Nonhuman primates